Reducing the Violent Behavior in Schizophrenia Patient Through Online Clinical Practice During the Covid-19 Pandemic - Rizki, Dhaifina Dini Ghassani; Wardani, Ice Yulia (Universitas Muhammadiyah Semarang, 2020)
Online clinical practice is an alternative in providing mental health services during the COVID-19 pandemic. Online clinical practice is useful in preventing relapse that is at risk of occurring during a pandemic in people with serious mental disorders such as schizophrenia. One of the schizophrenia relapse symptoms is a change in behavior that is distorted so that it creates a risk of violent behavior. Violence is a maladaptive response indicated by injuring oneself, others, or the environment. The patient’s ability to control violent behavior can be used as a means of preventing violent behavior. Nursing interventions based on mental health nursing care standards are carried out to prevent or control violent behavior in patient. The purpose of providing nursing care is to reduce symptoms and increase the patient’s ability to control violent behavior. The research method used case study analysis. The instrument used was an evaluation sheet of symptoms and the ability to control violent behavior. The final evaluation of the nursing care provided showed a decrease in symptoms and an increase in patient’s ability to control violent behavior. Promotion and prevention of health problems in patient with a risk of violent behavior can be done by implementing online nursing care based on mental health nursing care standards, as well as collaborating with clinical nurse specialist and related communities.